(untitled) (International Journal of Biomedical and Advance Research, 2019)
Background: Salivary gland lesions are quite common in people of all age groups. Clinical examination alone is not able to differentiate between them and pinpoint the exact cause. There are many salivary gland imaging can be used but the ultrasonography (USG) is a non-radiation, inexpensive, and readily available imaging technique that can be used to make diagnosis of salivary gland lesions. Hence the present study was undertaken to estimate the utility of ultrasonography in the diagnosis of chronic salivary gland lesions. Method: In this study, total 42 cases of various salivary gland lesions were evaluated by detail history, clinical, USG and histopathological examination. Histopathological reports were compared with USG findings. Results: Most of the salivary gland lesions were involving the parotid gland (59.5%), common in males (57.14%) and mostly in the age group of 31-40 years (23.81%). Based on ultrasonography, 15 cases (35.71%) were non-neoplastic and 27 cases (64.29%) were diagnosed as neoplastic lesions. Among the neoplastic lesions, 21 (77.78%) cases were of benign tumors, 05 (18.52%) of malignant tumors and 01 (3.7%) case was suspicious for malignancy. Based on histopathology, 14 cases (33.3%) were non-neoplastic and 28 (66.7%) were neoplastic. Among the neoplastic lesions, 23 (82.14%) cases were of benign tumors and 05 (17.85%) cases were of malignant tumors. Sensitivity, specificity and diagnostic accuracy of USG of salivary gland lesions were 89.29%, 85.71% and88.09% respectively. Conclusion: USG should be used for initial assessment of all salivary gland lesions preoperatively to avoid open biopsy. However accurate and confirmatory diagnosis is given by histopathology.